Americanismos en "Los gallinazos sin plumas" (1955) de Julio Ramón Ribeyro - Serrano, Juan (2020)
In La expresión americana (American Expression) (1957), the Cuban poet José Lezama Lima adapts the concept of baroque, which he understands as a principle that characterizes Latin American cultural history. The author of Paradiso theorizes the cultural history of the continent and emphasizes thelandscape as a component of its identity. On the other hand, it is usual to see the author of Alienación (Alienation) as a marginal writer, however, the observations to the text are framed within the historical stage in which it is inscribed, from a shared American feeling. In this sense, we analyze a set of Americanisms to explore the meanings of the words. The Diccionario de americanismos (DA, 2010) (Dictionary of Americanisms) of the Asociación de Academias de la Lengua Española (ASALE) (Association of Spanish Language Academies) is used for the analysis.